Butanol production from Saccharina japonica hydrolysate by engineered Clostridium tyrobutyricum: The effects of pretreatment method and heat shock protein overexpression. (September 2021) - Fu, Hongxin; Hu, Jialei; Guo, Xiaolong; Feng, Jun; Yang, Shang-Tian; Wang, Jufang
Graphical abstract: Highlights: Butanol production from S. japonica hydrolysate by C. tyrobutyricum was studied. The effect of pretreatment method on butanol production was investigated. Ultrasonic-assisted acid hydrolysis was proposed for efficient butanol production. Heat shock protein overexpression was employed for enhanced butanol production. The highest butanol production from macroalgal biomass was obtained by Ct-pMA12G. Abstract: Macroalgal biomass is currently considered as a potential candidate for biofuel production. In this study, the effects of pretreatment method and heat shock protein overexpression were investigated for efficient butanol production from Saccharina japonica using engineered Clostridium tyrobutyricum . First, various pretreatment methods including acid hydrolysis, acid hydrolysis and enzymatic saccharification, and ultrasonic-assisted acid hydrolysis were employed to obtain the fermentable sugars, and the resulted hydrolysates were evaluated for butanol fermentation. The results showed that ultrasonic-assisted acid hydrolysate obtained the highest butanol yield (0.26 g/g) and productivity (0.19 g/L⋅h). Then, the effects of homologous or heterologous heat shock protein overexpression on butanol production and tolerance were examined. Among all the engineered strains, Ct-pMA12G exhibited improved butanol tolerance and enhanced butanol production (12.15 g/L butanol with a yield of 0.34 g/g and productivity of 0.15 g/L⋅h) from 1.8-fold concentrated S. japonica hydrolysate, which was the highest level ever reported for macroalgal biomass.